Perbedaan Pendapatan Pedagang Sebelum dan Sesudah Adanya Tol Cipali Di Sepanjang Jalur Pantura Desa Eretan Kabupaten Indramayu - Hasyim Asyari, Wahid (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2022)
This study aims to determine differences in the income of traders along Jalan Pantura, Eretan Kulon Village, Indramayu after the operation of the Cipali Toll Road. The research method used in this research is to use quantitative methods by comparing the level of income before and after the construction of the Cipali toll road. The population in this study were 50 respondents and a population study. The analysis technique in this study used the paired T test.The results showed that there were differences in the level of income earned by traders and had an impact on livelihoods. Changes in income levels from the results of this study indicate that there is a decrease in the income of traders along the Eretan Pantura Line with an average reduction of Rp.5,544,000 per month, this is experienced by all respondents in this study consisting of grocery store traders, automotive services, to the restaurant. Changes in income from these respondents were accompanied by differences in spatial patterns along the Indramayu Pantura Line, especially the Eretan Wetan Village, which was previously a pattern for the restaurant industry which promises to close because of a lack of customers, this spatial change is a reciprocal impact of road construction. Cipali toll road.